The influence of innovation and entrepreneurship education in higher education institutions on the development of students’ innovative thinking - Zuolong, Ye; Hernandez, Alexander A.; Yiwen, Wei (Edelweiss Applied Science and Technology, 2025)
This study focuses on the impact mechanism of innovation and entrepreneurship education in higher education institutions on students' innovative thinking. The aim is to address current issues in education, such as the disconnect between curricula and industry needs and the insufficient cultivation of innovative thinking skills. By establishing an "input - transformation - output" framework, this research explores the pathways of action and the moderating effects of core elements. An empirical approach is employed in this study. With 550 questionnaires collected from college students as the sample, analytical tools such as structural equation modeling are utilized to test the hypotheses. The findings indicate that the curriculum system positively influences the fluency and flexibility of thinking through knowledge integration. Practical activities enhance the originality of thinking via metacognitive development, and campus culture strengthens the criticality of thinking by motivating students. Specifically, the professional background moderates the relationship between knowledge integration and thinking flexibility, with a more pronounced effect observed in science and engineering majors compared to liberal arts and history majors. Moreover, personality openness moderates the relationship between motivation arousal and thinking criticality, with a more significant effect among individuals with higher levels of openness. This research reveals the specific impact mechanisms, offering a practical paradigm for refining innovation and entrepreneurship education theories and cultivating innovative talents.